2004
DOI: 10.1051/0004-6361:20031689
|View full text |Cite
|
Sign up to set email alerts
|

Polarimetric evolution of V838 Monocerotis

Abstract: Abstract. We present the results of our polarimetric and spectropolarimetric monitoring of V838 Monocerotis, performed at the Asiago and Crimean observatories during and after the multiple outbursts that occurred in January−March 2002. The polarization of the object is mainly due to interstellar polarization (P ∼ 2.48%). Intrinsic polarization up to ∼0.7% at 5000 Å is present during the second maximum of the object (February 2002). This intrinsic component increases toward shorter wavelengths but our limited s… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 20 publications
1
23
1
Order By: Relevance
“…As well as the finding of Chesneau et al (2014), evidence for a non-spherical morphology comes from Wisniewksi et al (2003b). They found that spectroscopic and spectropolarimetric variations took place during the outburst, this being indicative of asymmetric geometry; this result is backed up the study of Desidera et al (2004), who also found polarimetric changes during 2002. Further polarisation variations were observed a few months after the outburst by Wisniewski et al (2003a), again suggesting the presence of an asymmetrical geometry of scattering material close to the star, and moreover that the distribution of this material had experience significant changes.…”
Section: Point Sourcementioning
confidence: 75%
“…As well as the finding of Chesneau et al (2014), evidence for a non-spherical morphology comes from Wisniewksi et al (2003b). They found that spectroscopic and spectropolarimetric variations took place during the outburst, this being indicative of asymmetric geometry; this result is backed up the study of Desidera et al (2004), who also found polarimetric changes during 2002. Further polarisation variations were observed a few months after the outburst by Wisniewski et al (2003a), again suggesting the presence of an asymmetrical geometry of scattering material close to the star, and moreover that the distribution of this material had experience significant changes.…”
Section: Point Sourcementioning
confidence: 75%
“…The enhanced flux at 18.1, 24, and 70 mm we observed in 2007 suggests that the equally strong (2007 epoch) 11.2 mm flux might not represent an additional enhancement of gas-phase molecular emission above that suggested by Lynch et al (2004) but rather represents a warm thermal dust emission component. Early postoutburst polarimetric observations (Wisniewski et al 2003a;Desidera et al 2004) indicated this ejecta was asymmetric; hence, we suggest that it is likely that dust which condenses from this ejecta will be spatially nonuniform and/or clumpy. We speculate that it is possible that one or more of these clumps eclipsed the line of sight in late 2006, producing the attenuation event reported by Bond (2006) and Munari et al (2007b).…”
Section: Bϫv Vmentioning
confidence: 80%
“…It is also likely that the ejecta are not uniformly distributed, and hence the binary morphology preferred by the data may be "clumpiness" in the ejecta. In this context, we note that polarimetric observations during the outburst (Desidera et al 2004;Wisniewski et al 2003) indicate that the source became significantly polarized (0.7% at 5000 ). This A has been interpreted as being due to departures from spherical symmetry during the outburst.…”
Section: ϫ013 ϫ1mentioning
confidence: 83%